2012
DOI: 10.1021/jm301328h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of α-Thymidine Analogues as Novel Antimalarials

Abstract: Plasmodium falciparum thymidylate kinase (PfTMPK) is a key enzyme in pyrimidine nucleotide biosynthesis. 3-Trifluoromethyl-4-chloro-phenyl-urea-α-thymidine has been reported as an inhibitor of Mycobacterium tuberculosis TMPK (MtTMPK). Starting from this point, we designed, synthesized and evaluated a number of thymidine analogues as antimalarials. Both 5′-urea-α- and β-thymidine derivatives were moderate inhibitors of PfTMPK and furthermore showed moderate inhibition of parasite growth. The structure of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 29 publications
0
51
0
Order By: Relevance
“…The SYBR Green protocol was used as a confirmatory counter-assay in a 96-well plate format [ 25 ]. This assay quantifies DNA (number of parasites) and thus allows to disregard extracts that interfere or are inhibitors in the LDH assay.…”
Section: Resultsmentioning
confidence: 99%
“…The SYBR Green protocol was used as a confirmatory counter-assay in a 96-well plate format [ 25 ]. This assay quantifies DNA (number of parasites) and thus allows to disregard extracts that interfere or are inhibitors in the LDH assay.…”
Section: Resultsmentioning
confidence: 99%
“…The active site architecture of Pf TMPK and human TMPK are highly conserved, but key differences in the Ploop (substrate recognition) and LID domains (active-site cover) suggest that selective compounds could be designed [112]. Cui et al [114] investigated selective inhibitors of the Mycobacterium tuberculosis TMPK [115] for activity against Pf TMPK, and found that α-thymidine analogues ( Figure 2) show moderate activity and weak growth inhibition of cultured P. falciparum. Subsequent crystal structures of Pf TMPK in complex with inhibitors demonstrated that the thymidine ring mimics that of the TMP substrate, the deoxyribose ring acts to orient the thymidine into an enclosed region of the pocket, and bound water molecules illustrate potential regions to target in compound elaboration [113].…”
Section: Tmpk (Thymidylate Kinase)mentioning
confidence: 99%
“…For eukaryotic parasites, most of the inhibitor studies have been conducted against Plasmodium falciparum TMK (PfTMK). Carbocyclic nucleoside analogues, modified thymine base analogues and thymidine urea derivatives have been tested for inhibitory effect on PfTMK (Kato et al, 2012;Kandeel et al, 2009;Cui et al, 2012). In case of prokaryotic TMKs various compounds such as modified thymine base, 3 substituted nucleosides and nucleotides, 2 ,3 bicyclic analogues, thymidine 5 -O-monophosphate analogues, substituted benzyl thymine analogues and acyclic nucleoside analogues were tested against Mycobacterium tuberculosis Vanheusden et al, 2002Vanheusden et al, , 2003Vanheusden et al, 2004;Van Daele et al, 2006;Gasse et al, 2007;Familiar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%